Supported cluster catalysts synthesized to be small, simple, selective, and stable. (14th June 2018) - Guan, Erjia; Fang, Chia-Yu; Yang, Dong; Wang, Liang; Xiao, Feng-Shou; Gates, Bruce C.
Abstract : Molecular metal complexes on supports have drawn wide attention as catalysts offering new properties and opportunities for precise synthesis to make uniform catalytic species that can be understood in depth. Abstract : Molecular metal complexes on supports have drawn wide attention as catalysts offering new properties and opportunities for precise synthesis to make uniform catalytic species that can be understood in depth. Here we highlight advances in research with catalysts that are a step more complex than those incorporating single, isolated metal atoms on supports. These more complex catalysts consist of supported noble metal clusters and supported metal oxide clusters, and our emphasis is placed on some of the simplest and best-defined of these catalysts, made by precise synthesis, usually with organometallic precursors. Characterization of these catalysts by spectroscopic, microscopic, and theoretical methods is leading to rapid progress in fundamental understanding of catalyst structure and function, and to expansion of this class of materials. The simplest supported metal clusters incorporate two metal atoms each—they are pair-site catalysts. These and clusters containing several metal atoms have reactivities determined by the metal nuclearity, the ligands on the metal, and the supports, which themselves are ligands. Metal oxide clusters are also included in the discussion presented here, with Zr6 O8 clusters that are nodes in metal–organic frameworks being among those that are understood the best. The surface and catalytic chemistries of these metal oxide clusters are distinct from those of bulk zirconia. A challenge in using any supported cluster catalysts is associated with their possible sintering, and recent research shows how metal nanoparticles can be encapsulated in sheaths with well-defined porous structures—zeolites—that make them highly resistant to sintering.